2012
DOI: 10.29252/jnkums.4.1.121
|View full text |Cite
|
Sign up to set email alerts
|

Impact of familiar sensory stimulation on level of Consciousness in patients with head injury in ICU

Abstract: Background & Objectives: Sensory deprivation is one of the complications threatening the comatose patients. Sensory stimulation is a treatment that awakes the brain's reticular activating system, which helps brain reorganization. This study aimed to investigate the impact of familiar sensory stimulation on level of Consciousness in patients with head injury in ICU. Material & Methods: This clinical trial was conducted on 60 patients with head injury in ICUs of Mashhad Emdadi Hospital. Intervention was the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Accordingly, patients' families are not just visitors, but they act as caregivers and partners in the treatment team, especially when making decisions (45). Hasanzadeh et al (46) stressed that the sensory stimulation of comatose patients by family members is an integral part of care that is overlooked in ICUs. As one of the resources available to perform sensory stimulations, patients' family members can voluntarily spend their time and energy for the recovery of their loved ones.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, patients' families are not just visitors, but they act as caregivers and partners in the treatment team, especially when making decisions (45). Hasanzadeh et al (46) stressed that the sensory stimulation of comatose patients by family members is an integral part of care that is overlooked in ICUs. As one of the resources available to perform sensory stimulations, patients' family members can voluntarily spend their time and energy for the recovery of their loved ones.…”
Section: Discussionmentioning
confidence: 99%
“…Bahonar et al showed that foot reflexology massage increased the level of consciousness of patients and reduced the duration of coma (19). Moreover, Hasanzadeh et al showed that familiar and early sensory stimulations increased the level of consciousness of TBI patients (20). Azimian et al also showed that foot massage increased the level of consciousness of comatose patients with TBI, and thus it can be used to increase the level of consciousness of comatose patients (21).…”
Section: Introductionmentioning
confidence: 99%
“…It may result in faster enhancement of the patient's cognitive status, improve the prognosis, and decrease the length of ICU stay. 39,40 However, there are still concerns about negative attitudes towards the family presence in the intensive care units and strict visiting policies that are applying in the almost Iranian hospitals. Therefore, more comprehensive studies in this regard can make grounds for changing the current attitude and providing more emotional support for patients and their families.…”
Section: Introductionmentioning
confidence: 99%